THE PURSUIT OF HAPPINESS UNDER DOMESTIC VIOLENCE AS REFLECTED ON NICHOLAS SPARK’S SAFE HAVEN - Pratiwi, Marisya; Widayanti, Maria Johana Ari; Margawati, Prayudias (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2018)
The objectives of this study are to find the motive of main character escape from her marriage and to explain how the main character struggle against life as reflected on Safe Haven novel. In doing this research, I used descriptive qualitative method because the data are taken in the form of words, sentences, utterances, and conversations made by the characters. There are several procedures to collect data; reading, identifying, inventorying, classifying, selecting and reporting. Millet's radical feminism theory was used to uncover some of the causes why domestic violence can occur, especially violence in women. The results of this study indicated that there is an existence of patriarchy system which controls social relationships within the family. The main character in this study tried to break the patriarchy system by escaping from her husband and changed all of her appearance. She started over her life in Southport in order to get her right which had been controlled by her husband. There she could live peacefully without violence and pressure. It also proved that women should use androgyny means they must have a side of masculinity to avoid being easily colonized and hurt by men in their private sphere.